2003
DOI: 10.1046/j.1365-2958.2003.03566.x
|View full text |Cite
|
Sign up to set email alerts
|

SOAP, a novel malaria ookinete protein involved in mosquito midgut invasion and oocyst development

Abstract: SummaryAn essential, but poorly understood part of malaria transmission by mosquitoes is the development of the ookinetes into the sporozoite-producing oocysts on the mosquito midgut wall. For successful oocyst formation newly formed ookinetes in the midgut lumen must enter, traverse, and exit the midgut epithelium to reach the midgut basal lamina, processes collectively known as midgut invasion. After invasion ookinete-to-oocyst transition must occur, a process believed to require ookinete interactions with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
132
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 137 publications
(136 citation statements)
references
References 44 publications
(81 reference statements)
2
132
0
2
Order By: Relevance
“…A cDNA library was made from the mRNA as described (5). Sequence analysis using the BLAST program showed that this database includes ESTs of known ookinete stage-specific genes: 33 circumsporozoite protein and thrombospondin-related anonymous protein-related protein (CTRP); 18 von Willebrand factor A domain-related protein; 91 chitinase; and 216 secreted ookinete adhesive protein (9)(10)(11)(12).…”
Section: Methodsmentioning
confidence: 99%
“…A cDNA library was made from the mRNA as described (5). Sequence analysis using the BLAST program showed that this database includes ESTs of known ookinete stage-specific genes: 33 circumsporozoite protein and thrombospondin-related anonymous protein-related protein (CTRP); 18 von Willebrand factor A domain-related protein; 91 chitinase; and 216 secreted ookinete adhesive protein (9)(10)(11)(12).…”
Section: Methodsmentioning
confidence: 99%
“…Other microneme proteins assigned to midgut traversal of P . berghei ookinetes include SOAP, WARP and CelTOS (cell‐traversal protein for ookinetes and sporozoites) (Yuda et al ., 2001; Dessens et al ., 2003; Kadota et al ., 2004; Li et al ., 2004; Kariu et al ., 2006; Ecker et al ., 2007, 2008; Kaneko et al ., 2015; Wirth et al ., 2015) (Table 1). …”
Section: The Zygote‐to‐ookinete Conversionmentioning
confidence: 99%
“…Moreover, it was later shown that the same laminin could also bind to the SOAP (Dessens et al, 2003) and CTRP (Mahairaki et al, 2005) proteins of the ookinete. In order to investigate whether these biochemical laminin-parasite interactions and the association described above also serve a biological role in the survival of the parasite during the invasion of the mosquito midgut by P. berghei parasites, we took advantage of the dsRNA gene silencing technology (Fire et al, 1998).…”
Section: Invasion and Oocyst Formation Are Influenced By Expression Ofmentioning
confidence: 99%
“…Although very thorough descriptions exist for this process involving two different organisms, the specific molecular partners that make these interactions possible have not yet been identified (see Sinden, 2002). Several ookinete surface molecules, such as P25 and P28 (Siden-Kiamos et al, 2000), SOAP (secreted ookinete adhesive protein; Dessens et al, 2003) and CTRP (circumsporozoite protein and thrombospondin-related adhesive protein; Dessens et al, 1999), have been implicated in the process of midgut invasion but, to date, no putative receptor has been identified or proposed on the midgut epithelium. Direct or indirect binding to Plasmodium surface proteins has only been demonstrated for laminin (Vlachou et al, 2001;Arrighi and Hurd, 2002;Dessens et al, 2003;Adini and Warburg, 1999) and collagen IV (Arrighi and Hurd, 2002;Adini and Warburg, 1999), both components of all vertebrate (Miosge, 2001) and invertebrate (Hynes and Zhao, 2000) basal laminae, including the one surrounding the insect midgut on its haemocoel side.…”
mentioning
confidence: 99%